Kalter Krieg Auf Dem Indischen Subkontinent : Die Deutsch-Deutsche Diplomatie Im Bangladeschkrieg 1971. - Benatar, Alexander (Berlin/Boston : Walter de Gruyter GmbH, 2020)
Die Reihe ZMO-Studien veröffentlicht Forschungsergebnisse, die das Forschungsprofil des Leibniz-Zentrum Moderner Orient reflektieren und ergänzen.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books